Modern methods of organic synthesis - Carruthers, William; Coldham, Lain (Cambridge: Cambridge University Press, 2004)
The fourth edition of this well-known textbook discusses the key methods used in organic synthesis, showing the value and scope of these methods and how they are used in the synthesis of complex molecules. All the text from the third edition has been revised, to produce a modern account of traditional methods and an up-to-date description of recent advancements in synthetic chemistry since the previous edition. A new chapter on the functionalisation of alkenes has been included and greater emphasis on highly stereoselective reactions and radical chemistry has been placed. Reference style has been improved to include footnotes on each page, allowing easy and rapid access to the primary literature. The book will be of significant interest to chemistry and biochemistry students at advanced undergraduate and graduate level, as well as researchers in academia and industry who wish to familiarise themselves with modern synthetic methods.
Index 483-497p.
Keywords: Organic compounds; Organic synthesis; General Science